PROFESSIONAL DOCUMENTARY AND AMATEUR VIDEOS ABOUT BAD ROADS OF THE RUSSIAN NORTH IN THE CONTEXT OF THE CULTURAL LANDSCAPE / ПРОФЕССИОНАЛЬНОЕ ДОКУМЕНТАЛЬНОЕ КИНО И «НАРОДНОЕ» ВИДЕО О БЕЗДОРОЖЬЕ СЕВЕРА В КОНТЕКСТЕ КУЛЬТУРНОГО ЛАНДШАФТА - LAVRENOVA OLGA A. / ЛАВРЕНОВА О.А. (Наука телевидения)
In the context of diverse studies of the cultural landscape, one of the important topics is the analysis of images of movement and traveling across spaces. Northern latitudes exacerbate this problem, and visual images become a vivid component of local socio-cultural practices and of ideas about these lands, shaped as a result of viewing documentary videos. Documentary has various levels, from spontaneous filming to professional non-fiction films. YouTube video hosting represents all of these levels. When included in some other, noncinema discourse, they become part of a holistic picture of reality, allowing a deeper understanding of many of its aspects. In this case—as part of the cultural landscapes of high latitudes, and more specifically—as a marker of the idea of movement, conquest, traveling through space. Professional documentary about the life of the indigenous peoples of the North includes such topics as migration, everyday traffic practices using traditional animal-drawn transport. The amateur videos dedicated to roads are shot on GoPro, DVRs, smartphones and mainly capture the challenges that drivers of heavy machinery face when struggling to get through mud and melted ice road. This is another plane of the cultural landscapes of the North, another culture, forming its own pattern of paths. These two cultures exist almost in parallel, but sometimes they intersect, creating points and zones of tension.